Normalization Transformations of Data in the Procedure of Statistical Methods Used in Education Research - Sławomir Pasikowski (Lubelski Rocznik Pedagogiczny, 2022)
Introduction: Sometimes the mapping of the variable values made during the measurement needs to be transformed due to the conditions related to the data analysis.